Bibliometric analysis of Helicobacter pylori vaccine development from 1993 to 2023 - Lei, Yeqing; Liu, Xiaochen; Du, Qin; Li, Yan (Frontiers in Microbiology, 2025)
BackgroundHelicobacter pylori infects half the global population and imposes a huge health burden. Developing a vaccine targeting H. pylori appears to be the most ideal preventive option. Based on Web of Science Core Collection (WoSCC) publications from 1993 to 2023, this study visually analyses the current status and trends of this field through bibliometric analysis.MethodsH. pylori vaccine-related articles and reviews were retrieved from WoSCC. Microsoft Excel, CiteSpace, and VOS viewer were used to analyze the data.Results1,199 publications from 1993 to 2023 were included in this bibliometric analysis. The results of this analysis show an overall upward trend in the number of publications and citations in this field. The United States is undoubtedly the most important contributor to this field in terms of publications, citation frequency, and national cooperation. Vaccine has the highest number of publications. Thomas F. Meyer is one of the leading scholars in the field. The most frequently cited article is “Immunization of mice with urease vaccine affords protection against H. pylori infection in the absence of antibodies and is mediated by MHC class II-restricted responses.” The literature and keyword analysis show that effective treatments and multi-epitope vaccines are focus area in this field. New antigen combinations (such as UreB, outer membrane vesicles, etc.) of H. pylori vaccines are novel research directions and frontiers.ConclusionOur study is the first bibliometric analysis of H. pylori vaccine research. By summarizing the current status of H. pylori vaccine research, our study highlighted the current research direction and frontier, providing valuable data for researchers to grasp the latest advancements and accelerate H. pylori vaccine development.